1990
DOI: 10.1177/074873049000500307
|View full text |Cite
|
Sign up to set email alerts
|

The Quail's Eye: A Biological Clock

Abstract: The site (intraocular vs. extraocular) of the biological clock driving a rhythm in melatonin content in the eyes of Japanese quail was investigated by alternately patching the left and right eyes of individual birds, otherwise held in constant light, for 12-hr periods. This patching protocol, therefore, exposed each eye to a light-dark cycle (LD 12:12) 180 degrees (12 hr) out of phase with the LD cycle experienced by the other eye. The optic nerves to both eyes were transected prior to initiating the patching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 27 publications
2
49
0
3
Order By: Relevance
“…These results suggest that extraretinally perceived light does not participate in photic entrainment of ocular melatonin rhythms. In Japanese quail, a light-entrainable circadian clock driving ocular melatonin rhythms has been shown to reside in the eyes [22]. Therefore it is likely that pigeons also have such a circadian clock within the eyes.…”
Section: Phase Control O F Circadian Melatonin Rhythms By Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that extraretinally perceived light does not participate in photic entrainment of ocular melatonin rhythms. In Japanese quail, a light-entrainable circadian clock driving ocular melatonin rhythms has been shown to reside in the eyes [22]. Therefore it is likely that pigeons also have such a circadian clock within the eyes.…”
Section: Phase Control O F Circadian Melatonin Rhythms By Lightmentioning
confidence: 99%
“…In mammals also, localization of ocular circadian oscillators has been shown by in vitro experi ment [23]. Although no in vitro evidence has been available, several lines of in vivo evidence have suggested that circadian oscillators are located in avian retina [22,24]. Because dopa mine is implicated in retinal melatonin synthe sis [10], we measured dopamine and melatonin release in the pigeon's eye in order to under stand circadian mechanisms of retinal mela tonin rhythms.…”
Section: Circadian Mechanisms Of Retinal Melatonin Rhythmsmentioning
confidence: 99%
“…The presence of another circadian oscillator in the hypothalamus is suggested by the fact that lesions which include the SCN also make birds arrhythmic (15). Although there is no published work on retinal rhythmicity in passerines, the retinas of some other birds (chickens, quail and pigeons) appear to synthesize melatonin rhythmically and probably contain circadian oscillators (16).…”
mentioning
confidence: 99%
“…A similar circadian regulation of melato nin production by local circadian oscillators (probably located in photoreceptor cells) has been reported in the retina of the hamster, Japanese quail, African clawed frog and zebrafish [7,[12][13][14][15]. Taken together, these re sults indicate, at least in some vertebrate spe cies including fish, that the retina harbors a circadian clock regulating melatonin rhythms and may play an important role in the circa dian organization.…”
Section: Melatonin Rhythms In Fishesmentioning
confidence: 51%